Made from Bone : Trickster Myths, Music, and History from the Amazon - Hill, Jonathan David, 1954- (Book collections on Project MUSE., 2009)
Recorded and transcribed by Jonathan Hill, this is a collection of mythic narratives from the indigenous Wakuenai of southernmost Venezuela. The central character throughout the tales is a trickster-creator, Made-from-Bone, who survives a prolonged series of life-threatening attacks.